SYNTHESIS OF THIN FILM OF TiO2 ON GRAPHITE SUBSTRATE BY CHEMICAL BATH DEPOSITION - Fitria Rahmawati; Sayekti Wahyuningsih; Pamularsih A.W (Indonesian Journal of Chemistry, 2006)
Thin film of TiO2 on graphite substrat has been prepared by means of chemical bath deposition. Cetyltrimethylammonium Bromide served  as linking agent of synthesized TiO2 to graphite substrate.The optical microscope and Scanning Electron Microscope (SEM) indicate that surfactant concentration affects the pore morphology of thin film Surface Area Analysis (SAA) of thin film indicated that the pore of thin film included in mesopore category. The anatase phase of TiO2 quantity arised as the surfactant concentration increase, gave high efficiency of induced photon conversion to current efficiency (% IPCE).